Sistem Informasi Berbasis Android untuk Meningkatkan Layanan Terhadap Alumni (Studi Kasus: Keluarga Mahasiswa Fakultas Teknik Uhamka) - Sri Fitriani; Firman Noor Hasan (Prosiding Seminar Nasional Teknoka, 2020)
Information technology is the main choice for creating an information system that is obtained accurately and precisely. The background of the Mobile App-based alumni information system, namely the UHAMKA Faculty of Engineering does not yet have a Mobile App-based information system for alumni who have graduated, with the Alumni application it can make it easier to find information such as job vacancies, events, important information announcements and can chat for Alumni. So it is less maximized in processing and developed. The purpose of this system is to design an information system based on Mobile App, the designof this system uses the Waterfall method which consists of needs analysis, system design, program syncode writing, Program Implementation and Testing, and System Maintenance, Creating Alumni application with profile features, features forum, forum detail feature, chat feature, and announcement feature with Mobile App. The results of this study were tested with the Black Box method, resulting in that the system gets 84.20% of student users. So it can be concluded that making Alumni applications can help Alumni get important information such as job vacancies, events and other announcements.